Fabrication of self‐healing hydrogel from quaternized N‐[3(dimethylamino)propyl]methacrylamide copolymer for antimicrobial and drug release applications. Issue 1 (20th June 2020) - An, Heng; Yang, Yan; Bo, Yunyi; Ma, Xiangbo; Wang, Yong; Liu, Longmei; Wang, Haijun; He, Yingna; Qin, Jianglei
Abstract: Self‐healing hydrogels have attracted great attention in recent years because of their wide application in bioscience and biotechnology. In this study, P(DMAPMA‐ stat ‐DAA) were synthesized by Reversible Addition‐Fragmentation Chain Transfer (RAFT) polymerization and quaternized to import antimicrobial properties. Then quaternized P(DMAPMA‐ stat ‐DAA) was used to prepare hydrogel containing acylhydrazone groups with Polyethylene oxide (PEO) diacylhydrazide as a cross‐linking agent. The acylhydrazone groups imparted a variety of properties, including group responsiveness and self‐healing properties to the hydrogel. At the same time, the quaternary ammonium endowed the hydrogel with the antimicrobial property. The mechanical property, self‐healing properties, and antimicrobial property of hydrogels were investigated intensively. Results showed hydrogels formed in neutral conditions, and the luminescent property was introduced with PEO23 dinaphthhydrazide (DNH) cross‐linking. The hydrogels showed a controlled pH‐sensitive DOX·HC l and Ovalbumin (OVA) release profile. In addition, the hydrogel showed the antimicrobial property and may have important applications in the biomedical field in the near future.